Thin Film Fluoropolymer Composite CMP Polishing Pad

JP7643839B2Active Publication Date: 2025-03-11DUPONT ELECTRONIC MATERIALS HLDG INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2020099553
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-10
Filing Date
2020-06-08
Publication Date
2025-03-11
Estimated Expiration
2040-06-08

AI Technical Summary

Benefits of technology

【0057】 実施例3 本発明の有益な効果を実証するために、PTFEおよびPFAを添加したおよび添加しなかった高強度試料Aパッドの一組に対して研磨試験を実施した。添加した各フルオロポリマーの濃度は、8.1%であった。Applied Materials Mirra CMP研磨ツール上、1試験当たり60個の200mmのTEOSモニタウェーハを使用して、各パッド組に対して3種のスラリーを試験した。使用したスラリーは、2種のセリアスラリー(Asahi CES333F2.5およびDA Nano STI2100F)およびヒュームドシリカスラリー(Cabot SS25)であった。使用した条件は、ダウンフォース3psi(20.7kPa)、プラテン速度93rpm、キャリア速度87rpm、およびスラリー流量150ml/分であった。コンディショナは、スラリーのタイプによって変更した。セリアスラリーについて、Saesol LPX-C4ダイヤモンドコンディショナディスクを使用した。シリカスラリーについて、Saesol AK45コンディショナディスクを使用した。すべてのコンディショナを7lbの力(3.2kgf)での研磨と同時に使用した。各ランについて、パッドブレークインコンディショニング工程を7lbの力(3.2kgf)で20分間使用して、均一な初期パッドテクスチャを確保した。研磨除去速度および欠陥性をまとめたものを以下の表2および2Aに示す。実施例3における研磨は、AsahiおよびDaNanoスラリーについてはセリアの等電点を下回るpHで、そして、SS25スラリーではシリカの等電点を上回るpHで行った。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643839000012
    Figure 0007643839000012
  • Figure 0007643839000013
    Figure 0007643839000013
  • Figure 0007643839000014
    Figure 0007643839000014
Patent Text Reader

Abstract

To provide a polymer-polymer composite polishing pad comprising a polishing layer having a polishing surface for polishing or planarizing a substrate.SOLUTION: A polymer matrix forms a polishing layer. Fluoropolymer particles are embedded in the polymer matrix. Diamond abrasive materials cut the fluoropolymer particles, rub the cut fluoropolymer against a patterned silicon wafer, and form a thin film covering at least a part of the polishing layer and having a zeta potential more negative than the polymer matrix at a pH of 7. The polishing surface formed from rubbing with the wafer has a fluorine concentration at a penetration depth of 1 to 10 nm of at least ten atomic percent higher than the bulk fluorine concentration at a penetration depth of 1 to 10 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] 2. Background of the Invention Chemical Mechanical Planarization (CMP) is a type of polishing process that is widely used to flatten or planarize layers of integrated circuit components to precisely build multi-layered three-dimensional electrical circuits. The layers to be polished are usually thin films (less than 10,000 angstroms) that have been deposited on an underlying substrate. The purpose of CMP is to remove excess material on the wafer surface to produce an extremely planar layer of uniform thickness, said uniformity extending across the entire wafer. Control of the removal rate and removal uniformity is of utmost importance.

[0002] CMP utilizes a liquid (often called a slurry) containing nano-sized particles. It is dispensed onto the surface of a rotating multi-layer polymer sheet or pad, which is mounted on a rotating platen. A wafer is mounted on an independent fixture or carrier with independent rotation means and pressed against the surface of the pad under a controlled load. This leads to a high speed relative motion between the wafer and the polishing pad (i.e., there is high speed shear at both the substrate and pad surface). Slurry particles trapped at the pad / wafer interface abrade the wafer surface, leading to removal. Various types of textures are incorporated into the top surface of the polishing pad to control speed, prevent hydroplaning, and efficiently transport the slurry under the wafer. Microscopic scale textures are produced by abrading the pad with various fine diamonds. This is done to control and increase the removal rate, and is commonly referred to as conditioning. Larger scale grooves of various patterns and dimensions (e.g., XY, circular, radial) are also incorporated for slurry transport adjustment.

[0003] The removal rate during CMP is calculated using Preston's law (rate = K p *P*V, where P is pressure, V is velocity, and K pis widely observed to follow the so-called Preston coefficient, which is a lumped sum constant that is characteristic of the consumable set used. K p Some of the most important contributing effects are provided below: (a) pad contact area (derived primarily from pad texture and surface mechanical properties); (b) the concentration of slurry particles at the contact area surface available for performing work; and (c) The rate of reaction between the surface particles and the surface of the layer to be polished.

[0004] Effect (a) is mainly determined by the nature of the pad and the conditioning process, effect (b) is determined by both the pad and the slurry, while effect (c) is mainly determined by the nature of the slurry.

[0005] The emergence of high capacity multi-layer memory devices (e.g., 3D NAND flash memory) has led to the need for further increases in removal rates. A key part of the 3D NAND manufacturing process consists of assembling a multi-layer stack of alternating SiO2 and Si3N4 films in a pyramidal staircase format. Once completed, the stack is capped with a thick SiO2 overlayer that must be planarized prior to completion of the device structure. This thick film is commonly referred to as a pre-metal dielectric (PMD). Device capacitance is proportional to the number of layers in the layered stack. Current commercially available devices use 32 and 64 layers, with the industry rapidly progressing to 128 layers. The thickness of each oxide / nitride pair in the stack is approximately 125 nm. Thus, the thickness of the stack increases directly with the number of layers (32=4,000 nm, 64=8,000 nm, 128=16,000 nm). For the PMD process, the total amount of capping dielectric to be removed is approximately equal to about 1 to about 1.5 times the stack thickness, assuming conformal deposition of the PMD.

[0006] Conventional dielectric CMP slurries have a removal rate of about 250 nm / min. This results in unnecessarily long CMP process times for the PMD step, which is currently a major bottleneck in the 3D NAND manufacturing process. As a result, there are many efforts to develop faster CMP processes. Most improvements have focused on process conditions (higher P and V), changes in the pad conditioning process, and improvements in slurry design (especially in ceria-based slurries). If an improved pad could be developed that could achieve higher removal rates in combination with existing processes and ceria slurries without introducing any negative effects, it would result in a significant improvement in CMP technology.

[0007] Hattori et al. (Proc. ISET07, p.953-4 (2007)) disclose comparative plots of zeta potential versus pH for various lanthanide particle dispersions, including ceria. The pH of zero charge (often called isoelectric pH) was measured to be about 6.6. Below this pH, the particles have a positive potential; above this pH, the particles have a negative potential. For inorganic particles such as silica and ceria, the isoelectric pH and the surface charge at pH above and below the isoelectric pH are determined by the acid / base equilibrium of the surface hydroxyl groups.

[0008] When polishing insulators with commercial ceria slurries and conventional pads, the electrostatic attraction between the particles and the pad gives rise to a characteristic rate dependence on particle concentration in the slurry. As discussed by Li et al. (Proceedings of 2015 Intl. Conf. on Planarization, Chandler, AZ, p. 273-27 (2015)), the concentration dependence of colloidal ceria particles on insulator polishing rate at a pH below the isoelectric pH of the slurry shows saturation behavior at very low particle concentrations (~1%). Above this concentration, adding more particles has no effect on the polishing rate. Systems in which the particle / pad interaction is repulsive do not exhibit such saturation behavior. The economic advantages of low particle concentration ceria slurries for insulator polishing have been the main driver for their commercial use, despite their relatively high price.

[0009] For dielectric CMP using silica-based slurries, most of the slurries used are alkaline, usually with a pH above 10. Silica particles have an isoelectric pH of about 2.2; as a result, they have a high negative charge at that slurry pH.

[0010] Prior art pad designs have generally left polymer modifications of the pad as a means to achieve increased speed. The primary methods used to achieve increased speed in CMP pads are as follows: a) optimizing the groove design without changing the composition of the top pad layer; b) modifying the conditioning process without changing the composition of the upper pad layer; c) providing a pad with a more desirable conditioning response by altering the conditioning response of the upper pad layer; and d) Providing a pad with an upper padding layer having a higher hardness or modified elasticity.

[0011] Despite all these solutions, a need remains to develop a planarizing polishing pad that increases removal rates for polishing with both anionic and cationic particle slurries without a significant increase in polishing defects.

[0012] Description of the invention One aspect of the present invention provides a polymer-polymer composite polishing pad useful for polishing or planarizing at least one of semiconductor, optical and magnetic substrates, comprising: a polishing layer having a polishing surface for polishing or planarizing the substrate; a polymer matrix forming the polishing layer, the polymer matrix having a tensile strength; and fluoropolymer particles embedded in the polymer matrix, the fluoropolymer particles having a tensile strength lower than that of the polymer matrix, wherein a diamond abrasive material cuts the fluoropolymer particles and rubs the cut fluoropolymer against a patterned silicon wafer to form a thin film covering at least a portion of the polishing layer and having a more negative zeta potential at pH 7 than the polymer matrix, and wherein the polishing surface formed from the friction with the wafer has a fluorine concentration (in atomic percent) as measured by X-ray photoelectron spectroscopy with a penetration depth of 1-10 nm that is at least 10 percent higher than the bulk fluorine concentration as measured by energy dispersive X-ray spectroscopy with a penetration depth of 1-10 μm.

[0013] Another aspect of the present invention provides a polymer-polymer composite polishing pad useful for polishing or planarizing at least one of semiconductor, optical and magnetic substrates, comprising: a polishing layer having a polishing surface for polishing or planarizing the substrate; a polymer matrix forming the polishing layer, the polymer matrix having a tensile strength; and fluoropolymer particles embedded in the polymer matrix, the fluoropolymer particles having a tensile strength lower than that of the polymer matrix, wherein a diamond abrasive material cuts the fluoropolymer particles and rubs the cut fluoropolymer against a patterned silicon wafer to form a thin film covering at least a portion of the polishing layer and having a more negative zeta potential at pH 7 than the polymer matrix, and wherein the polishing surface formed from friction with the wafer has a fluorine concentration (in atomic percent) as measured by X-ray photoelectron spectroscopy with a penetration depth of 1-10 nm that is at least 20 percent higher than the bulk fluorine concentration as measured by energy dispersive X-ray spectroscopy with a penetration depth of 1-10 μm, and the thin film does not cover the entire polishing surface during polishing. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a plot of contact angle versus PTFE loading for a polyurethane polishing pad. [Diagram 2] FIG. 2 is a measurement of the coefficient of friction data for a high strength polyurethane polishing pad versus a PTFE-containing version when produced with colloidal silica and colloidal ceria slurries. [Diagram 3] FIG. 3 is a plot of conditioner debris size for a high strength polyurethane polishing pad versus those obtained with PFA and PTFE additions. [Figure 4] FIG. 4 is a QCM plot showing the interactions between PFA and PTFE particles and ceria crystals. [Figure 5A] FIG. 5A is a plot of the TEOS removal rate (in Å / min) for a soft polyurethane polishing pad with no added PTFE particles. [Figure 5B] FIG. 5B is a plot of the TEOS removal rate (in Å / min) for a soft polyurethane polishing pad with added PTFE particles. [Figure 6] FIG. 6 is a plot of surface roughness for soft polyurethane polishing pads with and without the addition of PTFE particles.

[0015] Detailed Description of the Invention The present invention provides a polymer-polymer composite polishing pad useful for polishing or planarizing at least one of semiconductor, optical and magnetic substrates. The present invention is particularly useful for planarizing patterned silicon wafers with slurries containing cationic abrasive particles. A key element of the present invention is the modification of the upper pad surface properties to promote enhanced slurry particle adsorption to the upper surface by incorporation of fluoropolymer particles into the matrix of the polishing pad. An unexpected and novel effect in the pads of the present invention is that the addition of relatively low concentrations (approximately 1-20 wt% relative to the total polymer concentration) of low tensile strength fluoropolymer particles results in improved removal rates and a desirably high negative or positive surface zeta potential. Unless specifically stated otherwise, the present specification provides all concentrations in weight percent. Typically, the zeta potential of the fluoropolymer is more negative than the matrix when measured in distilled water at pH 7. This increased negativity can promote preferential attraction of positively charged particles to polishing asperities located on the polishing surface of the polishing pad during polishing. For purposes of this specification, positively charged particles include cationic particles such as ceria, titania, nitrogen-doped silica, aminosilane-coated silica, and particles modified with cationic surfactants. In particular, fluoropolymer-modified pads are very effective for polishing with ceria-containing slurries. The polishing surface is hydrophilic when measured with distilled water at a pH of 7, with an rms surface roughness of 10 μm after immersion in distilled water for 5 minutes. For example, at pH 7, polyurethanes will generally have a zeta potential in the range of -5 mV to -15 mV. The zeta potential of polyurethanes is usually positive at low pH levels and becomes negative with increasing pH levels. However, most fluoropolymers are hydrophobic and have a zeta potential of -20 mV to -50 mV at pH 7. The zeta potential of fluoropolymers tends to vary less with changes in pH levels than polyurethanes.

[0016] During polishing, a conditioner such as a diamond conditioning disk cuts the polishing pad, exposing fresh fluoropolymer at the surface. Some of this fluoropolymer spreads upwards, forming raised surface areas on the polishing pad. The wafer and fluoropolymer then rub against each other, forming a thin film on the polishing pad surface. This film tends to be fairly thin, such as 10 atomic layers thick or less. Because these films are so thin, they are not usually visible with a standard scanning electron microscope. However, the fluorine concentration of this film is visible with an X-ray photoelectron spectroscopy instrument, which can measure fluorine and carbon concentrations with a penetration depth of 1-10 nm. It is important that this film only covers a portion of the polishing surface. If the fluoropolymer film covers the entire surface, the polishing pad will remain hydrophobic during polishing. Unfortunately, these hydrophobic pads tend to provide poor polishing removal rates. In addition, it is also important that the polymer matrix maintains sufficient mechanical integrity to be able to facilitate smearing of the fluoropolymer onto the polymer matrix. For example, and most advantageously, slicing the polishing pad below the polishing surface and parallel to the polishing layer leaves one end of the fluoropolymer particles anchored in the polymer matrix while the other end is capable of plastically deforming at least 100% at elongation.

[0017] The polishing surface must contain enough matrix polymer at the polishing surface to wet the pad during polishing. This hydrophilic interaction between the polishing pad and the slurry is important to maintain efficient slurry distribution and polishing. For the purposes of this specification, a hydrophilic polishing surface refers to a polishing pad having an rms surface roughness of 10 μm after immersion in distilled water (pH 7) for 5 minutes. Diamond conditioning produces surface texture. Under some circumstances, it is possible to mimic diamond conditioning with an abrasive cloth such as sandpaper. Typically, a fluoropolymer film covers 20-80 percent of the polishing pad surface. A comparison of the fluorine concentration as measured by X-ray photoelectron spectroscopy and as measured by deep transmission energy dispersive X-ray spectroscopy with a penetration depth of 1-10 μm provides conclusive evidence of this film. The pad can produce a fluorine concentration at a penetration depth of 1-10 nm that is at least 10 atomic percent higher than in the bulk of the matrix measured at a penetration depth of 1-10 μm. Preferably, the pad is capable of producing a fluorine concentration, measured at a penetration depth of 1-10 nm, that is at least 20 atomic percent higher than in the bulk of the matrix, measured at a penetration depth of 1-10 μm.

[0018] Moreover, another unexpected effect of the addition of low tensile strength fluoropolymers at relatively low concentrations (approximately 1-20 wt% relative to the total polymer concentration) is that it results in a significant reduction in the size of the pad conditioning debris. However, fluoropolymer particles can function effectively when they comprise 2-30 volume percent of the polymer-polymer composite pad. This is believed to be responsible for the observed reduction in defectivity. Yet another unexpected and novel effect in the pads of the present invention is that the surface zeta potential of the pad can be modified by changing the specific fluoropolymer added to the parent polymer. This allows the pad to produce enhanced polishing rates for multiple types of slurries while maintaining a desirably small pad conditioning debris size, resulting in improved defect levels and maintaining the desirable properties of the parent pad in terms of planarization. In addition, the negative zeta potential can also help stabilize the slurry to limit harmful particle dropout that can result in harmful wafer scratching. Thus, this limiting of particle dropout can often result in lower polishing defects.

[0019] The addition of fluoropolymer particles to a parent polymer, such as a polyurethane block copolymer, forms a multipolymer composite. Preferably, the matrix is ​​a polyurethane block copolymer containing hard and soft segments. Unlike many other materials, the fluoropolymer exists as an independent polymer or phase without forming bonds or interlinks with the polyurethane matrix. The matrix may be either porous or non-porous. It is preferred that the fluoropolymer is significantly softer and more malleable than the surrounding matrix. It has been discovered that this low tensile strength allows the fluoropolymer to be smeared and form a thin film over the matrix. The combination of low tensile strength with smearing is essential to achieving good polishing results. Moreover, the addition of fluoropolymer weakens the polishing pad, but reduces the amount of 1-10 μm debris particles formed during polishing. When small amounts (1-20% by weight) are added, the resulting material still has suitable mechanical properties for use as a polishing pad. However, the response to the pad conditioning process is quite different. In fact, the fluoropolymer is capable of 100% elongation when trapped at one end in the polishing matrix. These fluoropolymers tend to fill gaps between surface features and reduce surface roughness.

[0020] Fluorinated polymer particles (PTFE, PFA) when used as powders in commercial pad formulations have shown improvement in defectivity and polishing removal rates during polishing of semiconductor substrates with cationic abrasives. The chemical structures of acceptable fluorinated additives are as follows: (a) PTFE (Polytetrafluoroethylene) [ka] (b) PFA (copolymer of tetrafluoroethylene (TFE) and perfluoroalkyl vinyl ether (PFAVE)) [ka] (c) FEP (copolymer of tetrafluoroethylene (TFE) and hexafluoropropylene (HFP)) [ka] (d) PVF (polyvinyl fluoride) [ka]

[0021] Examples of additional acceptable fluoropolymers are ETFE (ethylene tetrafluoroethylene), PVDF (polyvinylidene fluoride) and ECTFE (ethylene chlorotrifluoroethylene). Preferably, the fluoropolymer is selected from PTFE, PFA, FEP, PVF, ETFE, ECTFE and combinations thereof.

[0022] Many hydrophobic hydrocarbon polymers, such as fluorine end-capped polytetrafluoroethylene (PTFE), have a high negative zeta potential in water, typically less than -20 mV, and are fairly hydrophobic with hydrostatic contact angles above 100°. However, the contact angle hysteresis is extremely low. The advancing, static, and receding contact angles in normal water are 110°, 110°, and 95°, respectively, i.e., the material surface remains highly hydrophobic. The explanation for PTFE's high negative zeta potential is simple and is due to the low surface polarity and the high degree of orientation of the water dipoles at the polymer surface. Other hydrophobic fluoropolymers, such as polyvinyl fluoride (PVF), have similar hydrostatic contact angles, but can have a high positive zeta potential in water, typically greater than +30 mV. PVF differs from PTFE in that it is much more polar. The positive zeta potential is due to the presence of nitrogen-containing polymerization initiators that decompose and end-cap the fluoropolymer. For example, the azo initiator can form cationic fluoropolymer particles for several fluoropolymers including PTFE, PFA, FEP, PVF, ETFE, ECTFE and combinations thereof. Most preferably, the cationic fluoropolymer is PVF.

[0023] In the conditioning process, diamond crystals embedded in a metal or ceramic matrix act as cutting tools, cutting into the pad and removing material, resulting in the formation of surface texture. There are two basic modes of diamond conditioning interaction: plastic deformation and fracture. While the type, size and number per unit area of ​​diamond particles can have an effect, the structure of the polishing pad has a much larger impact on the mode of material removal. At one extreme, a solid, tough polymer is expected to produce a mainly plastic mode of conditioning wear, producing fine grooves but not necessarily mass removal. At the other extreme, a brittle, glassy polymer favors pad removal via fracture, releasing a significant portion of the pad surface into the slurry. For polymer composites or foams, the volume fraction of the interstices or additives tends to shift the conditioning mode to fracture, since fewer pad-polymer bonds need to be broken to release a volume roughly equivalent to the interstices or second phase. For closed cell polyurethane foams currently used in CMP pads, the size of these fractured fragments is very large, usually several tens of microns in size. Since these pads are relatively hard polymers, particles in this size range are known to cause scratching damage to the polished wafer when they are trapped in the slurry film under pressure during CMP. For the pads of the present invention, the addition of fluoropolymer particles acts to further weaken the tensile strength of the material in the interstitial spaces between the cellular gaps, especially for small diameters, so they significantly reduce the size of the conditioning debris. This contributes to a reduction in scratch density during polishing.

[0024] When the fluoropolymer particles in the pad of the present invention are exposed to the pad surface during polishing, the high shear rate resulting from the relative motion of the pad and wafer, together with the low shear strength of the fluoropolymer particles, results in the plastic flow of the fluoropolymer to adjacent parts of the pad surface. Over time, this results in a thin, discontinuous fluoropolymer film on the wafer surface. At low levels of particle loading, this results in a non-uniform surface consisting of urethane-rich and fluoropolymer-rich regions. A polishing pad with this type of non-uniform surface has a significant polishing rate enhancement for polishing with oppositely charged particles. The effective zeta potential of this non-uniform surface is controlled by the fluoropolymer used and the relative coverage area. For example, the use of PTFE particles with negative zeta potential results in a pad surface with enhanced negative zeta potential compared to the parent polymer.

[0025] Similarly, the conditioning debris generated when the pad of the present invention is used will also be attracted to the slurry particles. Because these debris particles are small, the adsorption of the slurry particles is expected to lead to the formation of slurry particle / pad particle agglomerates. The polishing operation that forms these agglomerates is much less harmful than with conventional pads for two reasons. First, because the parent debris is much smaller, the resulting agglomerates will be correspondingly smaller. Second, the agglomerates are expected to have low bond strength due to the non-uniformity of their surfaces. Finally, the fluoropolymer can stabilize the slurry and retard particle settling. This can be important for ceria-containing slurries and other cationic slurries. For example, fluoropolymer particles have a settling susceptibility in slurries containing cationic particles, as follows: a) determine the settling slope (% / time) for the slurry; b) determine the settling slope (% / time) for the slurry + 0.1 wt% fluoropolymer particles; and c) slope a)-slope b) is ≧ 5% / time. Since the slurry only resides on the polishing pad for a limited time, small changes in gradient can provide a significant reduction in polishing defects.

[0026] The pads of the present invention can be used with a wide variety of slurries to achieve enhanced polishing rates and reduced defectivity through novel means of selecting the fluoropolymer additive to be incorporated and matching it with the slurry particles and pH.

[0027] A CMP polishing pad according to the present invention can be made by a method including: providing an isocyanate-terminated urethane prepolymer; separately providing a curable component; combining the isocyanate-terminated urethane prepolymer and the curable component to form a combination; reacting the combination to form a product; forming an abrasive layer from the product, e.g., by skiving the product to form an abrasive layer of a desired thickness, e.g., by machining it to groove the abrasive layer; and forming a chemical mechanical polishing pad with the abrasive layer.

[0028] The isocyanate-terminated urethane prepolymer used in forming the polishing layer of the chemical mechanical polishing pad of the present invention preferably comprises the reaction product of components including a prepolymer polyol mixture containing a multifunctional isocyanate and two or more components, one of which is a fluoropolymer powder. The fluoropolymer powder does not react with the isocyanate. Rather, the fluoropolymer powder is added to the prepolymer to produce a uniform dispersion before the final polymerization step.

[0029] The isocyanate-terminated urethane prepolymer used in forming the polishing layer of the chemical mechanical polishing pad of the present invention preferably comprises the reaction product of components including a prepolymer polyol mixture containing a multifunctional isocyanate and two or more components, one of which is a fluoropolymer powder. The fluoropolymer powder does not react with the isocyanate. Rather, the fluoropolymer powder is added to the prepolymer to produce a uniform dispersion before the final polymerization step.

[0030] The present invention works with a variety of polymer matrices, such as polyurethane, polybutadiene, polyethylene, polystyrene, polypropylene, polyester, polyacrylamide, polyvinyl alcohol, polyvinyl chloride, polysulfone and polycarbonate. Preferably, the matrix is ​​polyurethane. For the purposes of this specification, "polyurethane" refers to products derived from difunctional or polyfunctional isocyanates, such as polyetherurea, polyisocyanurate, polyurethane, polyurea, polyurethaneurea, copolymers thereof and mixtures thereof. Thus, the CMP polishing pad can be manufactured by a method including: providing an isocyanate-terminated urethane prepolymer; separately providing a curable component; and combining the isocyanate-terminated urethane prepolymer and the curable component to form a combination, and then reacting the combination to form a product. The polishing layer can be formed by skiving the cast polyurethane cake to a desired thickness and grooving or drilling the polishing layer. Optionally, the cake mold can be preheated with IR irradiation, induction or direct current to reduce product variability when casting the porous polyurethane matrix. Optionally, either a thermoplastic or a thermosetting polymer can be used, most preferably the polymer is a crosslinked thermosetting polymer.

[0031] Preferably, the polyfunctional isocyanate used in forming the polishing layer of the chemical mechanical polishing pad of the present invention is selected from the group consisting of aliphatic polyfunctional isocyanates, aromatic polyfunctional isocyanates, and mixtures thereof. More preferably, the polyfunctional isocyanate used in forming the polishing layer of the chemical mechanical polishing pad of the present invention is a diisocyanate selected from the group consisting of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, naphthalene-1,5-diisocyanate, tolidine diisocyanate, para-phenylene diisocyanate, xylylene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, cyclohexane diisocyanate, and mixtures thereof. Even more preferably, the polyfunctional isocyanate used in forming the polishing layer of the chemical mechanical polishing pad of the present invention is an isocyanate-terminated urethane prepolymer formed by the reaction of a diisocyanate with a prepolymer polyol.

[0032] Preferably, the isocyanate-terminated urethane prepolymer used in forming the polishing layer of the chemical mechanical polishing pad of the present invention has 2-12 wt% unreacted isocyanate (NCO) groups. More preferably, the isocyanate-terminated urethane prepolymer used in forming the polishing layer of the chemical mechanical polishing pad of the present invention has 2-10 wt% unreacted isocyanate (NCO) groups (even more preferably, 4-8 wt%; most preferably, 5-7 wt%).

[0033] Preferably, the prepolymer polyol used to form the multifunctional isocyanate-terminated urethane prepolymer is selected from the group consisting of diols, polyols, polyol diols, copolymers thereof and mixtures thereof.More preferably, the prepolymer polyol is selected from the group consisting of polyether polyols (e.g., poly(oxytetramethylene) glycol, poly(oxypropylene) glycol and mixtures thereof); polycarbonate polyols; polyester polyols; polycaprolactone polyols; mixtures thereof; and mixtures thereof with one or more low molecular weight polyols selected from the group consisting of ethylene glycol; 1,2-propylene glycol; 1,3-propylene glycol; 1,2-butanediol; 1,3-butanediol; 2-methyl-1,3-propanediol; 1,4-butanediol; neopentyl glycol; 1,5-pentanediol; 3-methyl-1,5-pentanediol; 1,6-hexanediol; diethylene glycol; dipropylene glycol; and tripropylene glycol. Even more preferably, the prepolymer polyol is selected from the group consisting of polytetramethylene ether glycol (PTMEG); ester-based polyols (such as ethylene adipate, butylene adipate); polypropylene ether glycol (PPG); polycaprolactone polyols; copolymers thereof; and mixtures thereof. Most preferably, the prepolymer polyol is selected from the group consisting of PTMEG and PPG.

[0034] Preferably, when the prepolymer polyol is PTMEG, the isocyanate-terminated urethane prepolymer has an unreacted isocyanate (NCO) concentration of 2 to 10 wt % (more preferably, 4 to 8 wt %; most preferably, 6 to 7 wt %). Examples of commercially available PTMEG-based isocyanate-terminated urethane prepolymers include Imuthane® prepolymers (available from COIM USA, Inc., e.g., PET-80A, PET-85A, PET-90A, PET-93A, PET-95A, PET-60D, PET-70D, PET-75D); Adiprene® prepolymers (available from Chemtura, e.g., LF800A, LF900A, LF910A, LF930A, LF931A, LF939A, LF950A, LF952A, LF600D, LF601D, LF650D, LF667, LF700D, LF750D, LF751D, LF752D, LF753D, and L325); Andur® prepolymers (available from Anderson Development Available from the Company, for example, 70APLF, 80APLF, 85APLF, 90APLF, 95APLF, 60DPLF, 70APLF, 75APLF).

[0035] Preferably, when the prepolymer polyol is PPG, the isocyanate-terminated urethane prepolymer has an unreacted isocyanate (NCO) concentration of 3-9 wt% (more preferably, 4-8 wt%, most preferably, 5-6 wt%). Examples of commercially available PPG-based isocyanate-terminated urethane prepolymers include Imuthane® prepolymers (available from COIM USA, Inc., e.g., PPT-80A, PPT-90A, PPT-95A, PPT-65D, PPT-75D); Adiprene® prepolymers (available from Chemtura, e.g., LFG963A, LFG964A, LFG740D); and Andur® prepolymers (available from Anderson Development Company, e.g., 8000APLF, 9500APLF, 6500DPLF, 7501DPLF).

[0036] Preferably, the isocyanate-terminated urethane prepolymer used in forming the polishing layer of the chemical mechanical polishing pad of the present invention is a low free isocyanate-terminated urethane prepolymer having a free toluene diisocyanate (TDI) monomer content of less than 0.1 wt %.

[0037] Non-TDI-based isocyanate-terminated urethane prepolymers can also be used. For example, isocyanate-terminated urethane prepolymers are acceptable, including those formed by the reaction of 4,4'-diphenylmethane diisocyanate (MDI) and a polyol such as polytetramethylene glycol (PTMEG) with any diol such as 1,4-butanediol (BDO). When such an isocyanate-terminated urethane prepolymer is used, the unreacted isocyanate (NCO) concentration is preferably 4-10 wt% (more preferably 4-10 wt%, most preferably 5-10 wt%). Examples of commercially available isocyanate-terminated urethane prepolymers in this category include Imuthane® prepolymers (available from COIM USA, Inc., e.g., 27-85A, 27-90A, 27-95A); Andur® prepolymers (available from Anderson Development Company, e.g., IE75AP, IE80AP, IE85AP, IE90AP, IE95AP, IE98AP); and Vibrathane® prepolymers (available from Chemtura, e.g., B625, B635, B821).

[0038] The polishing layer of the chemical mechanical polishing pad of the present invention may further contain a plurality of microelements. Preferably, the plurality of microelements are uniformly distributed throughout the polishing layer. Preferably, the plurality of microelements are selected from trapped air bubbles, hollow core polymeric materials, liquid-filled hollow core polymeric materials, water-soluble materials, and insoluble phase materials (e.g., mineral oil). More preferably, the plurality of microelements are selected from trapped air bubbles and hollow core polymeric materials that are uniformly distributed throughout the polishing layer. Preferably, the plurality of microelements have a weight average diameter of less than 150 μm (more preferably, less than 50 μm; most preferably, 10-50 μm). Preferably, the plurality of microelements include polymeric microballoons (e.g., Expancel® microspheres from Akzo Nobel) having a shell wall of either polyacrylonitrile or polyacrylonitrile copolymer. Preferably, the plurality of microelements are incorporated into the polishing layer with a porosity of 0-50% by volume (preferably, a porosity of 10-35% by volume). The volume percent porosity is determined by the difference between the specific gravity of the unfilled abrasive layer and the specific gravity of the abrasive layer containing microelements divided by the specific gravity of the unfilled abrasive layer. Preferably, the fluoropolymer particles have an average particle size smaller than the average spacing of the polymer microelements which improves particle distribution, reduces viscosity and facilitates casting.

[0039] The polishing layer of the CMP polishing pad of the present invention can be provided in both porous and non-porous (i.e., unfilled) configurations. Preferably, the polishing layer of the chemical mechanical polishing pad of the present invention has a surface roughness of 0.4 to 1.15 g / cm. 3 (more preferably, 0.70 to 1.0; as measured in accordance with ASTM D1622 (2014)).

[0040] Preferably, the polishing layer of the chemical mechanical polishing pad of the present invention exhibits a Shore D hardness of 28 to 75 when measured according to ASTM D2240 (2015).

[0041] Preferably, the abrasive layer has an average thickness of 20 to 150 mils (510 to 3,800 μm), more preferably, the abrasive layer has an average thickness of 30 to 125 mils (760 to 3,200 μm), even more preferably, 40 to 120 mils (1,000 to 3,000 μm), and most preferably, 50 to 100 mils (1,300 to 2,500 μm).

[0042] Preferably, the CMP polishing pad of the present invention is adapted to be coupled to a platen of a polishing machine. Preferably, the CMP polishing pad is adapted to be secured to the platen of a polishing machine. Preferably, the CMP polishing pad can be secured to the platen using at least one of a pressure sensitive adhesive and a vacuum.

[0043] The CMP polishing pad of the present invention optionally further comprises at least one additional layer coupled to the polishing layer. Preferably, the CMP polishing pad optionally further comprises a compressible base layer attached to the polishing layer. The compressible base layer preferably improves the conformability of the polishing layer to the surface of the substrate being polished.

[0044] The final CMP polishing pad of the present invention further includes the incorporation of textures of one or more dimensions on its upper surface. These can be classified as macro-textures or micro-textures according to their size. Common types of macro-textures used in CMP control hydrodynamic reactions and / or slurry transport and include grooves of many configurations and designs, including but not limited to annular, radial and cross-hatching. These can be formed into thin uniform sheets via machining or directly on the pad surface via net-shape forming processes. Common types of micro-textures are fine scale features that create surface asperities that are the contact points with the substrate wafer where polishing occurs. Common types of micro-textures include but are not limited to textures formed either before, during or after use by abrasion with many hard particles such as diamonds (often referred to as pad conditioning) and micro-textures formed during the pad fabrication process.

[0045] A critical step in a substrate polishing operation is to determine the end point of the process. One popular in-situ method for end point detection involves providing a polishing pad with a window that is transparent to a selected wavelength of light. During polishing, a light beam is sent through the window to the substrate surface, where it reflects and passes back through the window to a detector (e.g., a spectrophotometer). Based on the return signal, the characteristics of the substrate surface (e.g., the thickness of the film thereon) can be determined for the purpose of end point detection. To facilitate such light-based end point methods, the chemical mechanical polishing pad of the present invention optionally further comprises an end point detection window. Preferably, the end point detection window is selected from an integral window incorporated into the polishing layer; and a plug-placed end point detection window block incorporated into the chemical mechanical polishing pad. For unfilled pads of the present invention with sufficient transmittance, the top pad layer itself can be used as the window opening. If the polymer phase of the pad of the present invention exhibits phase separation, the cooling rate during fabrication can also be locally increased to create permeable regions of the upper pad material in order to locally inhibit phase separation, resulting in more permeable regions suitable for use as endpointing windows.

[0046] The CMP polishing pad is used with a polishing slurry as described in the background of the invention. The pad of the present invention can be used with a wide variety of slurries to achieve enhanced polishing rates and reduced defectivity by a novel means of selecting the fluoropolymer additive to be incorporated and matching it with the slurry particles and pH.

[0047] The CMP polishing pad of the present invention is designed for use with slurries whose pH is either above or below the isoelectric pH of the particles used. The maximum rate can be selected by choosing a fluoropolymer based on simple criteria. For example, CeO2 has an isoelectric pH of about 6.5. Below this pH, the particle surface has a net positive charge. Above this pH, the particles have a net negative charge. If the pH of the slurry is below the isoelectric pH of the slurry particles, selecting a pad containing a fluoropolymer particle addition (e.g., PTFE or PFA) with a negative zeta potential at that pH will provide the greatest improvement in removal rate. Similarly, for slurries using colloidal or fumed silica particles with a high pH (e.g., 10), the maximum polishing rate will be achieved by selecting a pad containing a fluoropolymer particle addition (i.e., PVF) with a positive zeta potential at that pH. This is a very attractive performance because it allows for rate enhancement for virtually any slurry.

[0048] A significant novel advantage of the pads of the present invention when used with silica slurries, as described in the background of the present invention, is that the additional effect of electrostatic attraction between the pads of the present invention and the silica particles can result in a significant reduction in the amount of particles used in the slurry, resulting in the polishing rates achieved with prior art pads, which provides a significant cost advantage to the user.

[0049] The CMP pads of the present invention may be manufactured by a variety of processes that are compatible with thermosetting urethanes. These include mixing the components as described above, pouring into a mold, annealing, and slicing into sheets of the desired thickness. Alternatively, they may be manufactured by more precise net shape molding. Preferred processes according to the present invention include: 1. thermosetting injection molding (often referred to as "reaction injection molding" or "RIM"), 2. thermoplastic or thermosetting injection blow molding, 3. compression molding, or 4. any similar type process in which a flowable material is placed and solidified to create at least a portion of the macro- or micro-texture of the pad. In one preferred molding embodiment of the present invention, 1. a flowable material is directed into or onto a structure or substrate; 2. as the material solidifies, the structure or substrate imparts the surface texture to the material, and 3. the structure or substrate is subsequently separated from the solidified material.

[0050] Hereafter, certain embodiments of the present invention will be described in detail in the following examples.

[0051] Example: Sample preparation Polishing pad samples, high strength polyurethane (sample A), medium porosity polyurethane with pore size of 40 μm (sample B), and low porosity polyurethane with pore size of 20 μm (sample C), were produced by varying the addition of four different commercially available fluoropolymer powders, PTFE-1 (Chemours Zonyl™ MP-1000 particles), PTFE-2 (Chemours Zonyl™ MP-1200 particles), PFA (Solvay P-7010, a copolymer particle of tetrafluoroethylene (TFE) and perfluoroalkyl vinyl ether (PFAVE)), and PVF (nitrogen-terminated polyvinyl fluoride particles) to the top pad material. From the manufacturer's data, the surface weighted average particle size was 1.6 μm for MP-1000 and 1.7 μm for MP-1200, compared to 8.9 μm for the PFA sample. The fluoropolymer powder was added to the prepolymer component of the polyurethane formulation to ensure uniform distribution in the final cured polyurethane prior to mixing with the curable component and the gas or liquid filled polymeric microelement component present in the pad. After preparation, equivalent pads with and without the fluoropolymer particles were prepared and tested.

[0052] Example 1 A set of samples A made with and without the addition of 10 weight percent PTFE-1 and PFA were characterized. As shown in the table below, the changes in characteristics were a decrease in tensile strength, hardness and most mechanical properties. Of particular interest was the difference between the effect of the addition on the shear storage modulus (G'), which was characteristic of elastic behavior, and the effect on the shear loss modulus (G''), which represents the amount of energy dissipated in the sample. The shear storage modulus G' at 40°C showed a significant decrease compared to the control (-31% for PFA and -45% for PTFE). The shear loss modulus G'' showed a similar trend (-26% for PFA and -37% for PTFE). Although all samples were primarily elastomeric polymers, tan δ, the ratio of G'' to G', increased by 6% and 14% for the PFA and PTFE additions, respectively. This was a direct measure of the increase in energy dissipation brought about by the fluoropolymer addition. A similar trend was observed for tensile strength, with a 6% decrease for the PFA addition and a 14% decrease for the PTFE addition.

[0053] [Table 1]

[0054] The data shows that the fluoropolymer doped materials have reduced physical properties compared to the parent materials, which indicated that the tensile strength of the fluoropolymer was less than that of the matrix of Sample A. Tensile strength was measured according to ASTM D412.

[0055] Microscopic analysis of the fluoropolymer doped pads revealed the presence of discrete fluoropolymer particles that were randomly distributed within the polymer matrix, as confirmed by EDS analysis. The fluorocarbon particles showed no evidence of attraction to or interaction with the flexible polymeric microelements that were also present.

[0056] Example 2 Deionized water contact angles were measured for a set of mesoporous polyurethane pads of sample B that had various amounts of PTFE-2 added during manufacture. As shown in Figure 1, the contact angle increased in direct proportion to the increasing PTFE content, to a plateau of around 140° at 7.5% PTFE content. All pads with both PTFE and PFA added were visibly more hydrophobic than the parent pad. Despite this, the polished surface is hydrophilic when measured using distilled water at pH 7, with an rms surface roughness of 10 μm after immersion in distilled water for 5 minutes.

[0057] Example 3 To demonstrate the beneficial effects of the present invention, polishing tests were performed on a set of high strength Sample A pads with and without the addition of PTFE and PFA. The concentration of each added fluoropolymer was 8.1%. Three slurries were tested for each set of pads on an Applied Materials Mirra CMP polishing tool, using 60 200 mm TEOS monitor wafers per test. The slurries used were two ceria slurries (Asahi CES333F2.5 and DA Nano STI2100F) and a fumed silica slurry (Cabot SS25). The conditions used were 3 psi (20.7 kPa) down force, 93 rpm platen speed, 87 rpm carrier speed, and 150 ml / min slurry flow rate. The conditioner was changed depending on the type of slurry. For the ceria slurry, a Saesol LPX-C4 diamond conditioner disk was used. For the silica slurry, a Saesol AK45 conditioner disk was used. All conditioners were used simultaneously with polishing at 7 lb force (3.2 kgf). A pad break-in conditioning step was used for each run for 20 minutes at 7 lb force (3.2 kgf) to ensure uniform initial pad texture. A summary of the polishing removal rates and defectivity is shown in Tables 2 and 2A below. Polishing in Example 3 was performed at a pH below the isoelectric point of ceria for the Asahi and DaNano slurries and above the isoelectric point of silica for the SS25 slurry.

[0058] [Table 2]

[0059] [Table 3]

[0060] When using a pad containing the fluoropolymer particles of the present invention with a cationic ceria-containing slurry, the polishing rate was substantially increased and the defect level, especially scratches and chatter marks, was substantially reduced. No such improvement was obtained when using an anionic silica-containing slurry. This charge-specific reaction with ceria to increase the rate and reduce the defects was unexpected.

[0061] To further understand the observed improvements, several tests were performed. A comparison of pad roughness after polishing for sample A with PFA additive showed reduced roughness compared to the control (18% reduction in rms roughness as measured by nanofocus laser profilometer). In addition, coefficient of friction (COF) measurements were performed during polishing with ceria-containing slurry (CES333F2.5) and silica-based slurry (Klebosol 1730) for high-strength pads with and without 8.1 wt% PTFE additive. Polishing conditions were the same as those used for the tests described in Tables 2 and 2A. As shown in Figure 2, for the silica slurry, there is no significant difference in COF between the control and PTFE samples over the downforce range tested. For the ceria slurry, higher COF was observed for both the control and PTFE samples. At higher downforces, no significant difference in COF was observed, indicating that the PTFE pad additive did not act as a lubricant. The PTFE samples had a fairly constant COF over the entire downforce range tested, while the control pad showed an increase in COF below 2 psi (13.8 kPa) of downforce, the difference being due to the lower roughness observed in the pad containing PTFE.

[0062] Another test was performed to further understand the effect of the fluoropolymer addition on the conditioning process. In this test, a Buehler benchtop polisher was used to mimic the effect of the conditioning process. Pad samples were loaded and conditioned with deionized water using a Saesol AK45 conditioner disk used at 10 lb force (4.5 kgf) to mimic the effect of pad break-in. Flow-through samples were taken at the beginning and end of the break-in cycle and the particle size distribution was measured with an Accusizer particle analysis tool. As shown in Figure 3, a significant reduction in pad debris size distribution was observed for both the PTFE-containing and PFA-containing pads compared to the control pad. The most significant size reduction occurred for particles in the 1-10 micron range. This was consistent with the reduction in scratch defects when the two fluoropolymers were added to the parent pad.

[0063] While the tests outlined above may explain certain aspects of the defectivity improvements of the present invention, they do not explain the observed increase in polishing rate. Therefore, additional tests were performed.

[0064] The interaction between ceria (cerium oxide) and the fluoropolymer additives used in the pad samples was investigated using quartz crystal microbalance (QCM) measurements. During the QCM measurements, a dilute dispersion of PTFE and PFA particles in deionized water (pH 6) was passed through a flow cell containing ceria crystals. The adsorption of the particles to the ceria crystals was demonstrated by the increase in mass measured by the high-sensitivity microbalance. As shown in Figure 4, attractive interactions between the ceria crystals and several different sizes of PTFE / PFA particles were observed. As the zeta potential of the ceria crystals at the tested pH was positive, the results indicate that the fluoropolymer particles have a negative zeta potential. It showed an extremely negative zeta potential, which is driven by the hydrophobic surface and its effect on the water dipole orientation. This effect is very different from the (negative) zeta potential of polyurethane, which is driven by the structural hydroxyl groups present in the polymer chains.

[0065] The conclusion from this test and other data presented is that the presence of fluoropolymer particles on the pad surface helps increase the polishing rate by increasing the overall attraction of the ceria particles to the pad surface and therefore raising the overall number of particle / wafer interactions per unit time during polishing. This effect does not occur when negatively charged silica particles are used in the slurry because electrostatic repulsion prevents the desired high surface concentration of particles from occurring.

[0066] In addition, a Lumisizer dispersion analyzer settling study was used to evaluate the stability of the slurries. The dispersion analyzer was operated in accordance with ISO / TR 1309, ISO / TR 18811, ISO18747-1 and ISO13318-2. Samples of the slurries with and without the fluoropolymer additive were centrifuged and the light transmission through the samples was measured to determine how quickly the slurry particles settled. This is a measure of the stability of the slurry and therefore the flocculation. The slopes of the measurements with and without the 0.1 wt% additive are shown in Table 3. If the fluoropolymer particles are not wetted, a minimum amount of surfactant (e.g., Merpol™ A phosphate alcohol nonionic surfactant from Stepan Company) is required to wet the particles as needed to make them water soluble.

[0067] [Table 4]

[0068] The slopes for the samples with additives were consistently lower than those without additives, indicating that they settled slower and therefore were more stable. This indicated that the reduction in defects could also result from preventing ceria particle agglomeration for slurries containing ceria particles such as DANano and Asahi. The relative stability of silica slurries such as SS25 could explain the limited defectivity improvement seen with the fluoropolymer additive, as ceria is more prone to agglomeration.

[0069] Example 4 To further illustrate the role of fluoropolymer addition on pad surface properties during polishing, a series of pads were prepared using the low porosity polyurethane of Sample C as a reference and varying the addition of PTFE-2 particles. Each sample was polished using the process and slurry described in Example 3. Following polishing testing, the polished samples of each pad were analyzed via X-ray photoelectron spectroscopy (XPS) and energy dispersive X-ray spectroscopy (EDS) to obtain compositional information about the effectiveness of polishing. XPS has a surface penetration depth of about 1-10 nm, thereby making it an extremely sensitive method for determining the composition of the surface region, while EDS has a penetration depth of about 1-10 um and provides information about the bulk concentration.

[0070] [Table 5]

[0071] As shown in Table 4, the surface of the used pad containing fluoropolymer showed a substantial enrichment of fluorine at the outer surface compared to the bulk, which is strong evidence of the presence of a fluorocarbon film on the pad surface during polishing.

[0072] Example 5 To obtain more information about the characteristics of the polished pad surface layer of the pad of the present invention, polishing tests were performed on a control pad and a pad of the present invention containing 10 wt% PTFE. The overall process and slurry were as described in Example 3, and the polishing pad of Example 4 was used. For this test, three different conditioners were used to evaluate their effect on polishing rate and texture. Conditioner AB45 is a conditioner developed for use with ceria slurries, which results in a low roughness pad surface. Conditioner AK45 is a more aggressive conditioner with a higher density of larger diamonds. Conditioner LPX-V1 is a very aggressive conditioner using a combination of large and small diamonds. After polishing, the surface texture of the used pad was examined using a nanofocus non-contact laser profilometer.

[0073] FIG. 5A shows the TEOS removal rate of the prior art control pad for each of the three conditioners tested at three different polishing pressures (2, 3 and 4 psi, 13.8, 20.7 and 27.6 kPa). The low roughness conditioner provided the highest removal rate, with little difference in rate effect for the other two conditioners. For the pad of the present invention (FIG. 5B), the polishing rates for all three conditioners were significantly higher for all three conditioners compared to the control.

[0074] Profiling measurements were performed at the center of the polished area using a nanofocus confocal 3D surface metrology tool. A comparison of the root mean square (rms) roughness measured according to ISO 25178 for each pad and conditioner is shown in Figure 6. For the prior art control pad, the RMS roughness increased in proportion to the aggressiveness of the conditioner. In contrast, the RMS roughness of the pad of the present invention was significantly lower for all conditioners.

[0075] Example 6 To further illustrate the importance of zeta potential to the rate of fluoropolymer addition, pads prepared with particle addition of PVF were evaluated for zeta potential and polishing performance using the same silica- and ceria-based commercial slurries used in Example 3. As shown in Table 5 below, the zeta potentials for the additive and nitrogen-terminated PVF used in the pads of Example 3 are significantly different.

[0076] [Table 6]

[0077] The zeta potential of the PVF used was strongly positive, while the zeta potential of PTFE and PFA was largely negative. The addition of cationic PVF to the pad of the present invention resulted in a non-uniform surface containing areas of positive and negative surface charge. Despite the overall pad surface being electrically negative, the resulting pad surface provided attraction of negatively charged slurry particles, for example, colloidal silica, with a corresponding increase in polishing rate. Similarly, charge repulsion for positively charged slurry particles, such as ceria, resulted in a reduced removal rate in slurries whose pH was below the isoelectric pH of the particles, due to a reduced area of ​​attraction on the pad surface and a corresponding reduction in active slurry particles on the pad contact surface.

[0078] Therefore, comparative polishing tests were performed using samples of the low porosity polyurethane polishing pads of Sample C with and without the addition of 10 wt% PVF during sample preparation. These pads were used to polish TEOS wafers using the same conditions as those used in Example 3.

[0079] [Table 7]

[0080] As can be seen from Table 6, the polishing rate results showed an opposite trend to Example 4, i.e., the pad of the present invention having a cationic additive enhanced the rate of the negatively charged silica slurry, while decreasing the rate when used with a slurry having positively charged particles.

[0081] The polymer-polymer composite polishing pad of the present invention provides an unexpectedly large increase in polishing removal rate with a large reduction in polishing defects. A relatively small amount of fluoropolymer particles covers a smaller surface area instead of the entire surface, increasing polishing efficiency without compromising the hydrophilic surface of the polishing pad necessary for efficient slurry distribution.

Claims

1. a polishing layer having a polishing surface for polishing or planarizing a substrate; A polyurethane matrix forming a polishing layer, the polyurethane matrix having tensile strength; and 1. A polymer-polymer composite polishing pad useful for polishing or planarizing at least one of semiconductor, optical and magnetic substrates, comprising fluoropolymer particles embedded in a polyurethane matrix, the fluoropolymer particles being hydrophobic and having a tensile strength less than that of the polyurethane matrix, wherein a diamond abrasive material cuts the fluoropolymer particles, a thin film covers at least a portion, but not all, of a smaller polishing surface of the polishing layer, the thin film having a more negative zeta potential at pH 7 than the polyurethane matrix, and the polishing surface having the thin film has a fluorine concentration (in atomic percent) as measured by X-ray photoelectron spectroscopy with a penetration depth of 1-10 nm that is at least 10 percent higher than the bulk fluorine concentration as measured by energy dispersive X-ray spectroscopy with a penetration depth of 1-10 μm, and the polishing surface is hydrophilic when the contact angle is measured with distilled water at pH 7 after 5 minutes immersion in distilled water and conditioned to a rms surface roughness of 10 μm.

2. a polishing layer having a polishing surface for polishing or planarizing a substrate; A polyurethane matrix forming a polishing layer, the polyurethane matrix having tensile strength; and 1. A polymer-polymer composite polishing pad useful for polishing or planarizing at least one of semiconductor, optical and magnetic substrates, comprising fluoropolymer particles embedded in a polyurethane matrix, the fluoropolymer particles being hydrophobic and constituting 2-30 volume percent of the polymer-polymer composite polishing pad and having a tensile strength lower than that of the polyurethane matrix, wherein a diamond abrasive material cuts through the fluoropolymer particles, a thin film covers at least a portion, but not all, of the polishing layer's smaller polishing surface, the thin film having a more negative zeta potential at pH 7 than the polyurethane matrix, and the polishing surface having the thin film has a fluorine concentration (in atomic percent) as measured by X-ray photoelectron spectroscopy with a penetration depth of 1-10 nm that is at least 20 percent higher than the bulk fluorine concentration as measured by energy dispersive X-ray spectroscopy with a penetration depth of 1-10 μm, and the polishing surface is hydrophilic when the contact angle is measured with distilled water at pH 7 after 5 minutes immersion in distilled water and conditioned to a rms surface roughness of 10 μm.

3. 3. The polymer-polymer composite polishing pad of claim 2, wherein the polishing pad is sliced ​​below the polishing surface and parallel to the polishing layer, leaving one end of the fluoropolymer particles anchored in the polyurethane matrix and the other end capable of plastically deforming at least 100% in elongation.

Citation Information

Patent Citations

  • Polishing pad, polyurethane layer for polishing pad, and method of polishing silicon wafer

    JP2015130521A

  • Low friction planarizing / polishing pads and use thereof

    US20050042976A1